Relationship between academic pressure and mobile game addiction among middle school students： mediating role of self-control - Gou Yunjie; Sun Chongyong; Li Lingcan; Lu Dandan; Wang Nanqing; Bai Wenfeng (Sichuan jingshen weisheng, 2022)
ObjectiveTo explore the current status of academic stress， self-control and mobile game addiction among middle school students， and to test the mediating role of self-control.MethodsA total of 750 middle school students were enrolled by convenient sampling method， and were assessed using Academic Pressure Questionnaire， Self-Control Scale （SCS） and Mobile Game Addiction Scale. Thereafter， the mediating effect of self-control on the association between academic stress and mobile game addiction was analyzed with PROCESS mediating effect test.ResultsA total of 682 middle school students completed the survey. The scores of Academic Pressure Questionnaire， SCS and Mobile Game Addiction Scale of the selected middle school students were （58.56±11.34）， （38.42±6.94） and （34.23±12.14）， respectively. The total score and each dimension score of Academic Pressure Questionnaire were positively correlated with the total score of Mobile Game Addiction Scale （r=0.189~0.259， P<0.01）， and negatively correlated with the SCS score （r=-0.348~-0.196， P<0.01）. The total score and each dimension score of Mobile Game Addiction Scale were negatively correlated with SCS score （r=-0.336~-0.252， P<0.01）. Academic stress could predict self-control negatively （β=-0.205， t=-9.288， P<0.01） and predict mobile game addiction positively （β=0.281， t=7.084， P<0.01）. Meantime， self-control could predict mobile game addiction negatively （β=-0.480， t=-7.238， P<0.01）. With self-control as a mediator variable， academic stress still significantly predicted the mobile game addiction （β=0.182， t=4.492， P<0.01）.ConclusionThe academic pressure， self-control and mobile game addiction of middle school students are all at the lower middle level， moreover， self-control has a partial mediating effect between academic pressure and mobile game addiction.